2012
DOI: 10.4161/hv.20211
|View full text |Cite
|
Sign up to set email alerts
|

The immunogenicity and safety of an investigational meningococcal serogroups A, C, W-135 and Y tetanus toxoid conjugate vaccine (ACWY-TT) compared with a licensed meningococcal tetravalent polysaccharide vaccine

Abstract: Immunogenicity and safety of ACWY-TT compared with licensed ACWY polysaccharide vaccine (MenPS) in healthy adults, and lot-to-lot consistency of three ACWY-TT lots were evaluated in a phase 3, open, controlled study. Adults aged 18–55 y were randomized to receive ACWY-TT (one of three lots) or MenPS. Serum bactericidal antibodies (rSBA) were measured pre- and 1 mo post-vaccination. Adverse events (AEs) were assessed 4 d (solicited symptoms) and 31 d (unsolicited symptoms) post-vaccination. Serious AEs were rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
52
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 32 publications
(33 reference statements)
7
52
0
1
Order By: Relevance
“…Exploratory analyses showed that the rSBA GMTs evaluated with both GlaxoSmithKline and HPA assays for meningococcal serogroups A, W-135, and Y were higher in subjects vaccinated with MenACWY-TT than in those who received the Men-PS vaccine. These results are consistent with those obtained previously for adults 18 to 55 years of age (36). Exploratory analysis done on the results obtained with the HPA assay showed that the percentages of subjects with rSBA titers of Ն1:8 for serogroups C and Y and with rSBA titers of Ն1:128 for serogroups A, W-135, and Y were statistically significantly higher among subjects vaccinated with the MenACWY-TT lot with the lowest level of O-acetylation of the meningococcal serogroup A PS than among those who received the Men-PS vaccine.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Exploratory analyses showed that the rSBA GMTs evaluated with both GlaxoSmithKline and HPA assays for meningococcal serogroups A, W-135, and Y were higher in subjects vaccinated with MenACWY-TT than in those who received the Men-PS vaccine. These results are consistent with those obtained previously for adults 18 to 55 years of age (36). Exploratory analysis done on the results obtained with the HPA assay showed that the percentages of subjects with rSBA titers of Ն1:8 for serogroups C and Y and with rSBA titers of Ն1:128 for serogroups A, W-135, and Y were statistically significantly higher among subjects vaccinated with the MenACWY-TT lot with the lowest level of O-acetylation of the meningococcal serogroup A PS than among those who received the Men-PS vaccine.…”
Section: Discussionsupporting
confidence: 94%
“…Pain at the injection site tended to be reported more frequently for participants who received the MenACWY-TT vaccine than the Men-PS vaccine. This observation is consistent with previous studies showing that injection site reactions are more frequent in individuals vaccinated with MenACWY-TT versus Men-PS (35,36,45,46) and those vaccinated with other quadrivalent meningococcal conjugate vaccines versus plain PS vaccines (47,48). It is likely that the increased reactogenicity following vaccination with the MenACWY-TT vaccine is due to the TT component (49).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar results have also been demonstrated in studies conducted in Asia and continental Europe which compared a quadrivalent tetanus toxoid conjugate meningococcal vaccine and MenACWY-PS (16)(17)(18). The differences seen in the current study may relate to geographical variations in meningococcal nasopharyngeal carriage between the United Kingdom study population and those from previous studies leading to differential degrees of natural priming or may be due to differences in the comparator polysaccharide vaccine used.…”
Section: Discussionsupporting
confidence: 85%